A participatory, qualitative analysis of the use of MagicSchool AI for course design - Tilak, Shantanu; Lincoln, Jesse; Miner, Tara; Christensen, Natasha; Jankowski, Judy; Kennedy, Kadie (Journal of Sociocybernetics, 2024)
This participatory study recounts conversational practices occurring between three teachers, a head of school, and a researcher during a month-long curriculum design workshop mediated by the MagicSchool AI technology to create social studies, language arts, science, and mathematics lessons for a virtual special education program. A social paradigm of AI-mediated educational practices is presented, wherein teachers interact with AI tools by embodying co-agency and a spirit of inquiry. Collective practices are interpreted using Gordon Pask’s conversation theory framework, showcasing how to design systems of human-AI feedback loops devoted towards curriculum design. Meeting transcriptions, AI-prompt data, AI-mediated lesson plans, teacher feedback, and final products are shared using narrative inquiry to illustrate how collaborative co-agency culminated in lesson plans that co-observers felt confident in deploying.